The effectiveness of extension methods for the development of self-reliance of agroforestry farmer groups in accelerating Forestry Development - Sarintan Efratani Damanik; Triastuti (CV. AFDIFAL MAJU BERKAH, 2022)
The ability of forestry extension agents, forestry extension materials to be delivered and the intensity of the extension are classified as effective. In terms of developing farmers ' independence and making extension workers more confident in assisting farmers. effective extension of agroforestry farmers, choosing extension materials must be strictly in accordance with the needs of the target in this case the main actors and agricultural businesses. The development of farmer groups is directed at improving the ability of agroforestry groups in carrying out their functions, namely increasing the ability of members to develop agribusiness. The existence of extension workers is the spearhead in the acceleration of Forestry Development has the skills to invite people to be more advanced and creative. The level of understanding of agroforestry farmers and the number of extension workers is still less effective, because the information and motivation of farmers is still lacking and the number of extension workers is not proportional to the number of farmer groups targeted by extension workers. Self-reliance development of agroforestry farmer groups to be achieved in Bongguron Village, Raya District, Simalungun Regency in order to realize independent and dynamic farmer groups, where farmers have discipline, responsibility and are skilled in cooperation to manage their business activities to increase forestry production, for this reason, a market with a high enough price is needed to market the production in order to restore the costs incurred by farmers in running their farming business and increase farmers ' income by increasing productivity so that it can support the acceleration of Forestry Development.